Business on a mission : how to build a sustainable brand - Last, Andy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Business on a Mission is a simple to follow guide for how organisations can adapt to the changing world and evolving expectations of stakeholders to build more purpose-led, sustainable businesses. It features proven models and case study examples of how to create a brand that talks to the emerging Gen Z consumer base; how to use social missions to drive sales in retail and with B2B customers; how to preserve reputation and licence to operate by working in partnership with not-for-profit organisations; and how to attract and retain the best talent by demonstrating a genuine social purpose. As well as clear, applicable models and behind-the-scenes descriptions of how successful campaigns were built and sustainable change made, the book features candid interviews with change makers from the worlds of retail, professional services, consumer goods and NGOs. This second edition looks at how businesses and brands like Dove are now linking social and environmental goals, with an exclusive interview with Unilever CEO, Alan Jope. It explores how investors are now driving a systemic change in focus in the boardroom towards the sustainability agenda, and how leaders can respond to this, featuring a new interview with Frank Cooper, Global Chief Marketing Officer and member of the Global Executive Committee at BlackRock. The impact of the pandemic on what it means to be a sustainable brand, including a focus on sustainable supply chains, the growing power of Gen Z, the growth of online purchasing, multi-stakeholder partnerships, increased regulation and culture at work is also explored. This book has been read, enjoyed and used by business leaders to identify models for change; by managers to create progressive campaigns; by NGOs to create stronger partnerships with the private sector; and by students to learn how theories of social purpose and sustainability can be applied in the real world. The first edition was Bronze winner of the AXIOM Business Book Award in the category of Philanthropy, Non-Profit, Sustainability"--
OCLC-licensed vendor bibliographic record.
Keywords: Branding (Marketing); Sustainability; Social responsibility of business; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Business Ethics